Global Structure of Positive Solutions for Some Second-Order Multipoint Boundary Value Problems - Hongyu Li; Junting Zhang (Journal of Function Spaces)
We investigate in this paper the following second-order multipoint boundary value problem: -(Lφ)(t)=λf(t,φ(t)), 0≤t≤1, φ′0=0, φ1=∑i=1m-2βiφηi. Under some conditions, we obtain global structure of positive solution set of this boundary value problem and the behavior of positive solutions with respect to parameter λ by using global bifurcation method. We also obtain the infinite interval of parameter λ about the existence of positive solution.